Estudio de factibilidad para la creación de una empresa productora y comercializadora de vestidos para niñas en la ciudad de Bogotá D.C. (2020)
The objective of this project is to develop a feasibility study for the creation of a company that produces and markets dresses for girls from 5 to 12 years old in the city of Bogota D.C., based on the idea of creating new trends for this product line, where there is the opportunity to market dresses that make a difference, so that it can contribute to the own needs of colors, designs, concepts and styles in children’s fashion.